PRECONCEPTION PREPARATION OF WOMEN AFTER LATE INDUCED ABORTION IN CONGENITAL MALFORMATIONS OF THE FETUS - Галина Владимировна Кривчик; Елена Николаевна Кравченко; Лариса Владимировна Куклина; Екатерина Валерьевна Коломбет (The Publishing House Medicine and Enlightenment, 2020)
Preconception preparation - a set of preventive measures aimed at minimizing the risks in the implementation of the reproductive function of a particular married couple. The aim of the research - to develop a complex of rehabilitation and preconception training of women after late induced abortion with congenital malformations of the fetus that are incompatible with life. Materials and methods. Rehabilitation and preconception training was carried out for 60 women after termination of pregnancy with CPR incompatible with life. All women were divided into 2 groups: patients of group B1 were given a comprehensive rehabilitation program, and group B2 - rehabilitation measures were limited to regulatory documents. The developed comprehensive post-abortion rehabilitation and pre-gravidar training included the following elements: 1. Prior to induced late abortion. 2. During induced abortion. 3. Post-abortion follow-up was followed by pre-gravidar training. Results. In order to assess the effectiveness of the comprehensive rehabilitation system, women were examined 3 months after a late induced abortion. in the future, women were re-examined for pre-gravidar training and identification of long-term consequences. Early complications of late induced abortion (bleeding, endometritis, hematometry, uterine subinvolution, cervical rupture) were observed in 3 (10 %) women in group B1 and 15 (50 %; p = 0.002) in group B2. Late complications (menstrual irregularities, endometrial hyperplasia, and chronic endometritis) were detected only in B2. In total, 3 (10 %) women in group B1 and 20 (66.7 %; p = 0.000) in group B2 had long-term complications of late abortion. Conclusion. The tactics of managing patients after artificial termination of pregnancy should include the preventive use of components of comprehensive rehabilitation and preconception training. For this purpose, the program of preventive measures should include the use of medications (COC, drugs that suppress lactation, folic acid subsidies, etc.), as well as physical therapy.